Alzheimer’s disease protective allele of Clusterin modulates neuronal excitability through lipid-droplet-mediated neuron-glia communication - Xiaojie Zhao; Yan Li; Siwei Zhang; Ari Sudwarts; Hanwen Zhang; Alena Kozlova; Matthew J. Moulton; Lindsey D. Goodman; Zhiping P. Pang; Alan R. Sanders; Hugo J. Bellen; Gopal Thinakaran; et al. (Molecular Neurodegeneration)
Abstract Background Genome-wide association studies (GWAS) of Alzheimer’s disease (AD) have identified a plethora of risk loci. However, the disease variants/genes and the underlying mechanisms have not been extensively studied. Methods Bulk ATAC-seq was performed in induced pluripotent stem cells (iPSCs) differentiated various brain cell types to identify allele-specific open chromatin (ASoC) SNPs. CRISPR-Cas9 editing generated isogenic pairs, which were then differentiated into glutamatergic neurons (iGlut). Transcriptomic analysis and functional studies of iGlut co-cultured with mouse astrocytes assessed neuronal excitability and lipid droplet formation. Results We identified a putative causal SNP of CLU that impacted neuronal chromatin accessibility to transcription-factor(s), with the AD protective allele upregulating neuronal CLU and promoting neuron excitability. And, neuronal CLU facilitated neuron-to-glia lipid transfer and astrocytic lipid droplet formation coupled with reactive oxygen species (ROS) accumulation. These changes caused astrocytes to uptake less glutamate thereby altering neuron excitability. Conclusions For a strong AD-associated locus near Clusterin (CLU), we connected an AD protective allele to a role of neuronal CLU in promoting neuron excitability through lipid-mediated neuron-glia communication. Our study provides insights into how CLU confers resilience to AD through neuron-glia interactions.